Unprecedented Fe(IV) Species in a Diheme Protein MauG: A Quantum Chemical Investigation on the Unusual Mössbauer Spectroscopic Properties - Ling, Yan (2010)
Ferryl species are important catalytic intermediates in heme enzymes. A recent experimental investigation of a diheme protein MauG reported the first case of using two Fe(IV) species as an alternative to compound I in catalysis. Both Fe(IV) species have unusual Mössbauer properties, which was found to originate from novel structural features based on a quantum chemical investigation. With comparison to the previously reported Fe(IV)=O and Fe(IV)–OH species, results here provide the first evidence of a couple of new mechanisms by which proteins influence the properties of ferryl species by directly providing the O via Tyr, or stabilizing exogenous O via hydrogen bonding interaction. These results expand our ability to identify and evaluate high-valent heme proteins and models.